La violencia familia y su relación con el rendimiento académico en los estudiantes de segundo grado de secundaria del colegio Experimental UNAP 2021 - Hidalgo Cuhello, Oriana Carmin (2022)
The general objective of the research was to determine the relationship that exists between family violence and the academic performance of the students of the second Grade of Secondary School of the UNAP Experimental School, 2021. The research was non-experimental. The general design of the research was Descriptive and Cross-sectional to the extent that we intend to describe each variable independently, to discover the relationship between family violence and how it is related to school performance. The population was made up of second grade high school students from the Experimental School UNAP of San Juan Bautista Educational Institution in 2021, making a total of 100. The sample consisted of second grade high school students from sections A and B, totaling 65 students, of which only 60 students were surveyed. The sample was selected randomly for convenience. The most important results were obtained through the inferential statistical test t-student (t), it was found that tc = 51.90> tt = 3.14, gl = 6, alpha = 1% and when applying the contingency coefficient, r = 68% was obtained. which indicates that the variables are moderately related, accepting the research hypothesis: "Family violence is directly related to the academic performance of 2nd grade high school students from the UNAP Experimental School, 2021",